2014
DOI: 10.1002/j.0022-0337.2014.78.1.tb05652.x
|View full text |Cite
|
Sign up to set email alerts
|

An Online Alcohol and Oral Health Curriculum for Dental Students

Abstract: Regular heavy alcohol use can cause or worsen several oral health disorders and is associated with complications during and after dental procedures. Dental student education should provide detailed knowledge of these issues together with skills needed to detect and counsel patients with unhealthy drinking patterns. This project was designed to develop and evaluate a ive-module, online program to teach dental students about alcohol and oral health, systemic and oral biological effects of heavy drinking, require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…23 Finally, studies have shown that students are more likely to adopt and perform effective management of substance use patients when subjected to mandatory competencies and adequate clinical mentoring by faculty. 19,20,24 Dental accreditation bodies should consider incorporating marijuana training into their competencies to promote widespread implementation of these strategies across dental school curriculums.…”
Section: Discussionmentioning
confidence: 99%
“…23 Finally, studies have shown that students are more likely to adopt and perform effective management of substance use patients when subjected to mandatory competencies and adequate clinical mentoring by faculty. 19,20,24 Dental accreditation bodies should consider incorporating marijuana training into their competencies to promote widespread implementation of these strategies across dental school curriculums.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of audiotaped interventions showed that even though the fidelity to the protocol was high with regard to providing simple feedback, there was less compliance in the motivational interviewing elements. Miller and colleagues designed and evaluated an online five‐module programme on alcohol and oral health to undergraduate dental students and showed significant changes in their knowledge, attitudes and behaviours. Although the results of this student course were very encouraging, no information was gathered on whether the training had any long‐term effects once the students had qualified as dentists.…”
Section: Discussionmentioning
confidence: 99%
“…Another option would be to implement a short online course in sleep medicine, with posted lectures and online assessments. An online alcohol intervention course piloted to dental students was found to significantly change their knowledge, attitudes, and behaviors, 31 demonstrating such a methodology is feasible for consideration. A third option would be to involve other health professions in education regarding sleep disorders, thus encouraging inter‐and intraprofessionalism.…”
Section: Discussionmentioning
confidence: 99%